Edukasi Gizi Berbasis Film Pendek untuk Meningkatkan Kebiasaan Makan dan Pengetahuan Remaja - Wulandari, Agnes Maharani Puji; Marlina, Paramitha Wirdani Ningsih (FORIKES, 2025)
Knowledge about nutrition is one of the causes of nutritional problems due to adolescent food choices and body image perceptions. Education using short films can be an alternative to solving knowledge and practice problems in adolescents. The purpose of this study was to test the effectiveness of education with short films to improve eating habits and knowledge in adolescents. The design of this study was pretest-posttest with control group. The sampling technique was by simple random sampling involving 74 adolescents, each group consisting of 37 people. Adolescents watched films together online 3 times with a duration of 7-8 minutes per series. The instruments used to measure the level of knowledge were balanced nutrition and body image questionnaires, while eating habits were measured by the Adolescent Food Habits Checklist (AFHC). Data analysis was carried out using the Wilcoxon test. The results of the analysis in the treatment group with short films showed that the p value for eating habits was 0.000 (there was a difference in eating habits between before and after the intervention); while the p value for knowledge was 0.001 (there was a difference in knowledge about balanced nutrition and body image between before and after the intervention). In the control group, the p-value for eating habits was 0.115 (no difference in eating habits between before and after the intervention); while the p-value for knowledge was 0.396 (no difference in knowledge about balanced nutrition and body image between before and after the intervention). Based on the results of the study, it was concluded that education using short films was successful in improving eating habits and knowledge about balanced nutrition and body image.Keywords: adolescents; nutrition education; short films; knowledge; balanced nutrition; body image; eating habits ABSTRAK Pengetahuan tentang gizi merupakan salah satu penyebab masalah gizi dikarenakan pemilihan jenis makanan remaja dan persepsi body image. Edukasi menggunakan film pendek dapat menjadi alternatif untuk penyelesaian masalah pengetahuan dan praktik pada remaja. Tujuan penelitian ini yaitu menguji efektivitas edukasi dengan film pendek untuk meningkatkan kebiasaan makan dan pengetahuan pada remaja. Desain penelitian ini yaitu pretest-posttest with control group. Teknik pengambilan sampel yaitu dengan cara simple random sampling yang melibatkan 74 remaja, masing-masing kelompok terdiri atas 37 orang. Remaja 3 kali menonton film bersama-sama secara online dengan durasi 7-8 menit per-series. Instrumen yang digunakan untuk mengukur tingkat pengetahuan adalah kuesioner gizi seimbang dan body image, sedangkan kebiasaan makan diukur dengan Adolescent Food Habits Checlist (AFHC). Analisis data dilakukan dengan uji Wilcoxon. Hasil analisis pada kelompok perlakuan dengan film pendek menunjukkan bahwa nilai p untuk kebiasaan makan adalah 0,000 (ada perbedaan kebiasaan makan antara sebelum dan sesudah intervensi); sedangkan nilai p untuk pengetahuan adalah 0,001 (ada perbedaan pengetahuan tentang gizi seimbang dan body image antara sebelum dan sesudah intervensi). Pada kelompok kontrol, nilai p untuk kebiasaan makan adalah 0,115 (tidak ada perbedaan kebiasaan makan antara sebelum dan sesudah intervensi); sedangkan nilai p untuk pengetahuan adalah 0,396 (tidak ada perbedaan pengetahuan tentang gizi seimbang dan body image antara sebelum dan sesudah intervensi). Berdasarkan hasil penelitian disimpulkan bahwa edukasi menggunakan film pendek berhasil meningkatkan kebiasaan makan dan pengetahuan tentang gizi seimbang dan body image.Kata kunci: remaja; edukasi gizi; film pendek; pengetahuan; gizi seimbang; body image; kebiasaan makan